Kuyper’s Spirituality in Its Calvin-Context - Vlastuin, W. van (Church history and religious culture, 2021)
Abstract This article explores Abraham Kuyper’s spirituality by comparing it to that of John Calvin. Calvin’s Institutes exhibits three dimensions of his spirituality in the context of the mystical union with Christ, namely, the affective character of this union, its effects and its significance for a correct estimation of the world. By comparison, Kuyper put a greater emphasis on the importance of the affections in mystical union because he gives more weight to the regenerated life. This focus also coheres with Kuyper’s more optimistic approach to the Christian life, which contrasts with Calvin’s emphasis on the need for daily justification. In Kuyper’s approach the indwelling of the Spirit represents the union between heaven and earth, while Calvin stresses that God’s future kingdom is beyond the here and now.